Tunnelling-induced ground displacements in sand - Zhou, Bo (2015)
The main objective of this research was to examine the effects that relative density and stratification have on greenfield soil displacements above tunnels in sandy ground. Data from a series of plane-strain centrifuge tests on tunnels in silica sand are presented. The relative density of the sand samples ranged from 90% to 50% in the tests. The soil displacement data were examined to determine features of greenfield settlement, both surface and subsurface. The effects that relative density and stratification have on the settlement trough shape is demonstrated and discussed. Some interesting features of tunnelling in sandy ground are revealed in the analysis.